Real-world evidence in patient-reported outcomes (PROs) of metastatic castrate-resistant prostate cancer (mCRPC) patients treated with abiraterone acetate + prednisone (AA+P) across Canada: Final results of COSMiC - Gotto, Geoffrey (Can Urol Assoc J, 2020)
INTRODUCTION: Abiraterone acetate plus prednisone (AA+P) has shown to significantly improve survival. COSMiC, a Canadian Observational Study in Metastatic Cancer of the Prostate, set out to prospectively amass real-world data on metastatic castration-resistant prostate cancer (mCRPC) patients managed with AA+P in Canada. Herein, we report their patient-reported outcomes (PROs). METHODS: After a median followup of 67.1 weeks, 254 patients were enrolled across 39 sites. Functional Assessment of Cancer Therapy-Prostate (FACT-P), Montreal Cognitive Assessment (MoCA), Brief Pain Inventory-Short Form (BPI-SF), Brief Fatigue Inventory (BFI), and Current Health Satisfaction in Prostate Cancer (CHS-PCa) were evaluated at baseline, as well as at weeks 12, 24, 48, and 72 after AA+P initiation. Descriptive analysis was used with continuous variables. Changes from baseline were summarized using mean (standard deviation [SD]). RESULTS: At a median age of 76.6 (8.94), baseline FACT-P total score was 111.3 (19.56) with no significant change in their functional status observed from baseline over time. The median baseline MoCA score was 25.2 (4.52), yet subsequent assessments showed an absence of cognitive decline while under treatment. Similarly, no meaningful changes were detected in BPI, BFI, and CHS-PCa during the 72-week study period, thus suggesting that patients’ PROs were well-maintained throughout AA+P treatment. Prostate-specific antigen (PSA) response with >50% decline was 66.4%. Safety profile was consistent with the known side effect of AA+P. CONCLUSIONS: COSMiC represents the largest Canadian mCRPC cohort treated with AA+P with real-world, prospective evaluation of PROs. This data demonstrated the maintenance in quality of life and cognitive status over the course of the study and underscores the importance of PRO use in this complex patient population.